2013
DOI: 10.5217/ir.2013.11.2.146
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Colonic Diverticulitis as a Complication of Colonoscopy

Abstract: Colonoscopy is a good diagnostic tool and facilitates treatment of various colonic diseases. Nevertheless, it can induce many serious complications such as perforation and hemorrhage. Diverticulitis has also been reported as a serious complication of colonoscopy, with an incidence ranging from 0.04% to 0.08%. A 44-year-old male with chronic hepatitis B was presented with general weakness, myalgia, and febrile sensation. After admission for evaluation, pneumonia detected in the left upper and lower lobe and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…3 In a systematic review of PCD literature, a prospective study, 4 retrospective cohort studies, and 4 case reports were included. 1,5,8,9,[11][12][13][14] It is worth mentioning that all the reported cases were published by US and Asia Pacific sites and none from UK practices. 5 Among the reviewed studies, the 4 case reports highlighted cases of PCD with atypical presentations, characterized by elevated inflammatory markers only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a systematic review of PCD literature, a prospective study, 4 retrospective cohort studies, and 4 case reports were included. 1,5,8,9,[11][12][13][14] It is worth mentioning that all the reported cases were published by US and Asia Pacific sites and none from UK practices. 5 Among the reviewed studies, the 4 case reports highlighted cases of PCD with atypical presentations, characterized by elevated inflammatory markers only.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of PCD literature, a prospective study, 4 retrospective cohort studies, and 4 case reports were included. 1,5,8,9,11-14 It is worth mentioning that all the reported cases were published by US and Asia Pacific sites and none from UK practices. 5…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the subsequent outpatient colonoscopy image for this patient demonstrating a large caliber blood vessel juxtaposed to a colonic diverticulum. While there have been several detailed clinical images of colonic diverticula [6][7][8] and bleeding diverticula published, few have clearly illustrated the close relationship with perforating vasculature [9]. Young-Fadok et al published clinical images of colonoscopy findings from a 57-year-old man who presented with micro-perforations of colonic diverticula [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ko et al 13) reported diverticulitis as a complication of colonoscopy requiring hospitalization in 5 of 21,375 patients. In Korea, only one case report was found as a complication after colonoscopy; this was diagnosed with CT and recovered with broad-spectrum antibiotics and bowel rest 4) . Diverticula are pouch-like structures of the colon, and seem to develop as a result of raised intracolonic pressure in certain areas of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Diverticulitis can also rarely occur as a complication 1) . The incidence of acute diverticulitis after colonoscopy is 0.04% to 0.08% 2,3) , and only one case report was found in Korea 4) . Although diverticulitis is one of the most common presentations of diverticular disease, it is very rare but can occur as a complication of colonoscopy.…”
Section: Introductionmentioning
confidence: 99%